A Positive Feedback Loop of Long Noncoding RNA LINC00152 and KLF5 Facilitates Breast Cancer Growth - Li, Qiang; Wang, Xiao; Zhou, Liheng; Jiang, Mingyun; Zhong, Guansheng; Xu, Shuguang; Zhang, Minjun; Zhang, Yigan; Liang, Xiaodong; Zhang, Lei; Tang, Jianming; Zhang, Haibo (Frontiers in Oncology, 2021)
The long noncoding RNA (lncRNA) LINC00152, also known as CYTOR, displays aberrant expression in various cancers. However, its clinical value and functional mechanisms in breast cancer remain insufficiently understood. Our study found that LINC00152 is significantly upregulated in breast cancer, and that it acts as an indicator of poor survival prognosis. Further studies revealed that LINC00152 knockdown suppresses cell proliferation and tumorigenicity in vitro and in vivo. Mechanistic analyses demonstrated that LINC00152 directly binds to KLF5 protein and increases KLF5 stability. Moreover, LINC00152 is also a KLF5-responsive lncRNA, and KLF5 activates LINC00152 transcription by directly binding to its promoter. Our study suggests that LINC00152 promotes tumor progression by interacting with KLF5. LINC00152 may be a valuable prognostic predictor for breast cancer, and the positive feedback loop of LINC00152-KLF5 could be a therapeutic target in pharmacological strategies.